Factors associated with lost to follow up in patients with brain tumours: A multi-centre study in Pakistan - Muhammad Usman Khalid; Mohammad Hamza Bajwa; Mashal Murad Shah; Syed Nabeel Zafar; Altaf Ali Laghari; Naveed Zaman Akhunzada; Saad bin Anis; Muhammad Faraz Raghib; Sameen Siddiqi; Syed Ather Enam (Journal of the Pakistan Medical Association, 2022)
Objective: To identify populations at risk for lost to follow-up while undergoing management of brain tumours in a low-resource setting. Methods: A retrospective study was conducted at the neurosurgical centre on patients presenting with a brain tumour from January 1, 2019, to December 31, 2019. Data on demographic characteristics, surgical characteristics, treatment, and outcomes such as mortality status, were collected by manual chart review. LTFU was defined as patients discontinuing clinical follow-up at the institute of surgical consultation within two years from the initial visit. Univariate (odds ratio) and multivariate (b-coefficient) logistic regression were used to determine factors' significance for LTFU. Results: From a total of 2750 patients from 32 centres, 1140 (41.4%) were LTFU during the study period. Of these 1140 LTFU patients, 156 (13.7%) were LTFU without any intervention, 984 (86.3%) were LTFU after the primary surgery, and 872 (76.5%) patients were LTFU without any adjuvant treatment. On univariate analysis annual hospital case volume (p< 0.001), older age group (15-39 years (p=0.037) and ?40 years (p= 0.016)), and non-surgical treatment (p<=0.026) correlated with a higher risk of LTFU. Belonging to the middle-class cohort was correlated with a better chance of follow up (p=0.001). Multivariate analysis demonstrated that larger centres had the largest b-coefficient of 1.53 (95% CI= 1.3-1.8, p< 0.001). Conclusion: Our study demonstrated that almost half of patients diagnosed with brain tumours were LTFU within two years of diagnosis. Larger centres, non-surgical treatment, and older age seem to be associated with higher LTFU. Identifying vulnerable populations will allow the need-based provision of care and follow-up to improve health outcomes. Keywords: Lost to follow-up, Brain neoplasms, Retrospective study, Epidemiology, Registries. Continue...